2011
DOI: 10.1007/s11248-011-9506-x
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of snakin-2 and extensin-like protein genes restricts pathogen invasiveness and enhances tolerance to Clavibacter michiganensis subsp. michiganensis in transgenic tomato (Solanum lycopersicum)

Abstract: Two tomato proteins were evaluated by over-expression in transgenic tomato for their ability to confer resistance to Clavibacter michiganensis subsp. michiganensis (Cmm). Snakin-2 (SN2) is a cysteine-rich peptide with broad-spectrum antimicrobial activity in vitro while extensin-like protein (ELP) is a major cell-wall hydroxyproline-rich glycoprotein linked with plant response to pathogen attack and wounding. Tomato plants, cultivar Mountain Fresh, were transformed via Agrobacterium tumefaciens harboring a bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(41 citation statements)
references
References 50 publications
1
38
1
1
Order By: Relevance
“…Enhanced resistance to pathogen infections has also been reported in plants that express snakin genes [28,29]. Snakin peptides are thus considered important candidates for producing biotic stress tolerance in crops.…”
Section: Hemolytic Assays Of Recombinant Sn-1mentioning
confidence: 98%
See 1 more Smart Citation
“…Enhanced resistance to pathogen infections has also been reported in plants that express snakin genes [28,29]. Snakin peptides are thus considered important candidates for producing biotic stress tolerance in crops.…”
Section: Hemolytic Assays Of Recombinant Sn-1mentioning
confidence: 98%
“…Both cause rapid aggregation of pathogens, although this response is not directly related with their antimicrobial activity [11,26]. Transgenic plants over-expressing the SN-1 and SN-2 genes have been shown to exhibit increased resistance to a wide range of invading phytopathogens [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Antibacterial experiments and in vivo experiments showed that potato Snakin-1 and Snakin-2 proteins have the anti-bacterial and -fungi capacity. 16,17,48,49,50 The CaSn protein of the pepper has the ability to anti-root-knot nematode (Meloidogyne spp.). 30 French bean Snakin-2-like protein may be formed an approximately 42 kDa protein complex (FBCBP) with the proline-rich protein PRP to participate in the plant defense process.…”
Section: Gasas Involve In Plant Growth and Development Processmentioning
confidence: 99%
“…A 1-cm stem section above the inoculation site was aseptically removed from the harvested plants and homogenized in 400 l of sterile 10 mM MgCl 2 using a Retsch MM400 Tissuelyser (Newton, PA). After complete homogenization, 600 l of sterile 10 mM MgCl 2 was added for a final volume of 1 ml (25). The solution was spun down at 400 ϫ g for 3 min (16).…”
Section: Methodsmentioning
confidence: 99%